2019
DOI: 10.1155/2019/5451290
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of BIRC5 in Lung Adenocarcinoma Lacking EGFR, KRAS, and ALK Mutations by Integrated Bioinformatics Analysis

Abstract: Objective. This study was aimed at investigating the prognostic significance of Baculoviral IAP repeat containing 5 (BIRC5) in lung adenocarcinoma (LAD) lacking EGFR, KRAS, and ALK mutations (triple-negative (TN) adenocarcinomas). Methods. The gene expression profiles were obtained from Gene Expression Omnibus (GEO). The identification of the differentially expressed genes (DEGs) was performed by GeneSpring GX. Gene set enrichment analysis (GSEA) was used to execute gene ontology function and pathway enrichmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 41 publications
(37 reference statements)
1
35
0
Order By: Relevance
“…After co-expression and correlation analysis using the Oncomine, bc-GenExMiner, and UCSC Xena web-based tools in the present study, we confirmed that CDC20 gene was positively correlated with BIRC5 expression. As a matter of fact, both CDC20 and BIRC5 were found to be co-expressed in lung adenocarcinoma, endometrial cancer, renal cell carcinoma, and thyroid carcinoma [31][32][33][34]. Given that cell cycle process is often coordinated with apoptotic proteins to maintain tissue homeostasis, silencing the expressions of cell cycle protein as well as anti-apoptotic proteins simultaneously could potentially lead to cell cycle arrest and reduce the proliferation of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…After co-expression and correlation analysis using the Oncomine, bc-GenExMiner, and UCSC Xena web-based tools in the present study, we confirmed that CDC20 gene was positively correlated with BIRC5 expression. As a matter of fact, both CDC20 and BIRC5 were found to be co-expressed in lung adenocarcinoma, endometrial cancer, renal cell carcinoma, and thyroid carcinoma [31][32][33][34]. Given that cell cycle process is often coordinated with apoptotic proteins to maintain tissue homeostasis, silencing the expressions of cell cycle protein as well as anti-apoptotic proteins simultaneously could potentially lead to cell cycle arrest and reduce the proliferation of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…BIRC5 (14.7 kb long) is a mitotic spindle checkpoint gene, present at the telomeric end of chromosome 17. It is a fundamental protein involved in the regulation of mitosis by mediating tumor cell proliferation via β-catenin pathway and tumor cell invasion and migration via TGF-β pathway and PI3K/AKT pathway and apoptosis due to its interaction with DNA damage repair proteins [39] along with several pathological conditions. It has been found to be upregulated in pancreatic cancer, breast cancer, hepatocarcinoma, esophageal carcinoma, and neuroblastoma, with poor clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested increased BIRC5 expression contributes to the negative outcomes of various cancers, such as breast, lung, colorectal, prostate, and ovarian cancer [7]. CAO et al [19] found that high BIRC5 expression is related to tumor progression and poor prognosis of lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%